Janice VanCleave's weather : mind-boggling experiments you can turn into science fair projects. - VanCleave, Janice Pratt (New York : John Wiley, 1995)
Text and pictures explain weather concepts and give step-by-step instructions for conducting experiments such as making a barometer, measuring wind speed, and recreating the greenhouse effect.
Includes index.
Spine title: Weather.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
7.0.
Keywords: Science exhibitions -- Juvenile literature; Science projects -- Juvenile literature; Science -- Experiments -- Methodology -- Juvenile literature; Weather -- Experiments -- Juvenile literature; Experiments; Science projects; Weather -- Experiments; Science exhibitions; Science projects; Science -- Experiments -- Methodology; Weather -- Experiments